Evaluating a motivational and psycho‐educational self‐help intervention for athletes with mild eating disorder symptoms: A mixed methods feasibility study. (15th February 2022) - Sandgren, Sebastian S.; Haycraft, Emma; Arcelus, Jon; Plateau, Carolyn R.
Abstract: Objective: The primary aim was to assess the feasibility of undertaking a study evaluating the novel Motivational and Psycho‐Educational Self‐Help Programme for Athletes with Mild Eating Disorder Symptoms (MOPED‐A). A mixed‐methods approach was adopted to explore the feasibility of recruiting and retaining participants, and to evaluate the acceptability of measures, procedures and the intervention. A secondary aim was to explore the potential efficacy of MOPED‐A in reducing athletes' eating disorder symptoms. Method: Thirty‐five athletes were recruited. Participation involved completing MOPED‐A over a 6‐week period and completing self‐report measures at baseline (T1), post‐intervention (T2) and 4‐week follow‐up (T3). A subsample ( n = 15) completed an interview at T2. Results: Retention was good throughout the study ( n = 28; 80%). Quantitative and qualitative feedback suggested the format, delivery, content and dosage of MOPED‐A were acceptable. Athletes valued that the intervention was tailored to them, and this facilitated both participation and completion. Over a third of participants reported disclosing their eating difficulties and deciding to seek further support. Large reductions in eating disorder symptoms were detected at T2 and sustained at T3. Conclusions: The MOPED‐A intervention can be feasibly implemented, is acceptable to participants, and demonstrates potential for reducing symptoms in athletes. A larger, controlled trial is warranted. Highlights: Participant recruitment to the study was feasible, and an acceptable proportion of participants were retained throughout the study. This is the first study to show that the format and delivery of a self‐help intervention is acceptable to athletes with mild eating disorder symptoms, and that athletes valued the intervention being tailored to them which facilitated participation and completion. The intervention demonstrates potential for reducing athletes' eating disorder symptoms.